Enhancement of optical code division multiple access system based on 2D ZCC/MD spectral/spatial code - Rima Matem; S. A. Aljunid; M. N Junita; C. B. M Rashidi; Israa Shihab Aqrab (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The combination of 1D zero cross correlation (ZCC) and 1D Multi Diagonal (MD) results a new two dimensional hybrid called 2D ZCC/MD code for spectral/spatial OCDMA system. The proposed code aims to enhance the functional qualities of Optical Code Division Multiple Access (OCDMA) and to overcome the limitations of one dimensional codes. In this paper,   2D ZCC/MD is evaluated at data rate; 622Mbps.  A comparison of the proposed 2D ZCC/MD code to 1D Random Diagonal (RD) and 1D Modified Double Weight (MDW) highlight that 2D ZCC/MD  can support  a large number of active  users even at the higher user bit rate. Furthermore, in term of effective power 2D ZCC/MD can achieve lower effective power.